A case study in text mining of discussion forum posts: Classification with bag of words and global vectors - Cichosz, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Despite the rapid growth of other types of social media, Internet discussion forums remain a highly popular communication channel and a useful source of text data for analyzing user interests and sentiments. Being suited to richer, deeper, and longer discussions than microblogging services, they particularly well reflect topics of long-term, persisting involvement and areas of specialized knowledge or experience. Discovering and characterizing such topics and areas by text mining algorithms is therefore an interesting and useful research direction.
Keywords: text mining; discussion forums; text representation; document classification; word embedding